Zinc contents in foods and estimates of dietary intakes in Guangzhou, Guangdong Province, China - Mai, Wenqiang; Wang, Fan; He, Shuyou; Wen, Yanmao; Yu, Guanghui; Zhang, Lei; Dong, Hanying (Frontiers in Nutrition, 2024)
Zinc is one of human essential metals. In this study, 101 kinds of daily food for residents, including vegetables, aquatic food, meat, fruits, rice and cereal products, pulse food, dairy products and eggs, were collected at various agricultural markets and supermarkets in Guangzhou city, China, and their zinc contents were determined. The results showed oyster is most abundant in zinc (703.5 ± 25.6 mg/kg), followed by high-zinc milk powder (58.63 ± 0.90 mg/kg), pulse food, mutton, beef and pig liver with zinc contents above 30 mg/kg. The zinc contents of rice and cereal products, milk powder, poultry, pork, some aquatic food and eggs are also relatively high (>10 mg/kg), while vegetables and fruits have zinc contents significantly below 10 mg/kg. The daily zinc intake per person was determined by considering the zinc content of various food types and the dietary habits of specific demographic groups, resulting in 12.3 mg/day for the normal person, 11.2 mg/day for low-income individual, 12.3 mg/day for middle-income individual, 13.3 mg/day for high-income individual, 10.2 mg/day for older individual, 12.9 mg/day for factory worker, 11.5 mg/day for college student, and 8.4 mg/day for kindergarten child. The reference values of zinc intake recommended by the Chinese Nutrition Society were used to evaluate the zinc intake of Guangzhou residents, showing that the residents’ zinc intake is generally sufficient and not necessary to use zinc supplementation. Income, age and occupation could have posed influence on dietary intake of zinc.